4z-8+2z=3z-9+5z

Simple and best practice solution for 4z-8+2z=3z-9+5z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4z-8+2z=3z-9+5z equation:


Simplifying
4z + -8 + 2z = 3z + -9 + 5z

Reorder the terms:
-8 + 4z + 2z = 3z + -9 + 5z

Combine like terms: 4z + 2z = 6z
-8 + 6z = 3z + -9 + 5z

Reorder the terms:
-8 + 6z = -9 + 3z + 5z

Combine like terms: 3z + 5z = 8z
-8 + 6z = -9 + 8z

Solving
-8 + 6z = -9 + 8z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-8z' to each side of the equation.
-8 + 6z + -8z = -9 + 8z + -8z

Combine like terms: 6z + -8z = -2z
-8 + -2z = -9 + 8z + -8z

Combine like terms: 8z + -8z = 0
-8 + -2z = -9 + 0
-8 + -2z = -9

Add '8' to each side of the equation.
-8 + 8 + -2z = -9 + 8

Combine like terms: -8 + 8 = 0
0 + -2z = -9 + 8
-2z = -9 + 8

Combine like terms: -9 + 8 = -1
-2z = -1

Divide each side by '-2'.
z = 0.5

Simplifying
z = 0.5

See similar equations:

| 3t^3-27t=0 | | 30x^8-7x^4-49=0 | | 13x+195=139(x+15) | | 3x+5=-25-10x | | 2x-2xy^2=0 | | x^6-x^3-42=0 | | 18x+12x^2+2x^3=0 | | 2n+5=15 | | 0=x^4-4x^3+7x^2-16x+12 | | 10m^5n^3+46m^5n^2+24m^5n=0 | | 4r^2+28r+49=0 | | 16+x=48 | | 2.1=0.8 | | 2.93x=92.96 | | 4(x+7)+2(x-5)= | | 16p-1(5p+6)=-8-2(1p+12) | | 21x^5-27x^4+6x^3=0 | | 3(x-9)+4(x+3)= | | 0.29(x+50)-6=0.4(3x+20) | | (x+3)+(y+6)=46 | | 4.2d=-10.5 | | 7k+5=5(1-7k) | | 3(x-4)+4(x+3)= | | 48-2x=x | | .25x-0.75=-0.25x+3.25 | | x-16+2x-85+.5x+8=180 | | 7-14x=15x-16 | | 3x+y=78 | | -27t=-21.6 | | 14x^2+7x-21=0 | | -5y=8.5 | | 5t^2+15t+10=0 |

Equations solver categories